Inhibition of barley root growth by Actinomycin D: Effects on mitotic activity, protein content and peroxidase activity - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2007)
The responses of root growth, mitotic activity, starch and protein content as well as peroxidase activity to antitumoral antibiotic Actinomycin D (ActD) were investigated with time- and dose-dependent experiments in barley (Hordeum vulgare L. cv. Efes). The seeds were treated with 5 and 50 mu g/ml ActD for 48, 72 and 96 h. Seed germination was not significantly affected by ActD, but the root growth was strongly inhibited. ActD at high concentration induced abnormal root morphology. Although the mitotic index decreased approximately by 50% in low concentration, it was zero in hi-h concentration at 48 h. Various types of mitotic aberrations, such as stickiness, chromosome bridges, binucleate cells, micronucleus formation and cell death, were observed in ActD-treated root tips. ActD induced an enhancement of peroxidase activity, whereas it reduced the starch and total protein content. The present results indicate that the inhibition of barley root growth after ActD treatment is a complex phenomenon due to reduction of starch and protein contents and mitotic index, accompanied by induction of cell death, chromosomal aberrations and POD activity.
Keywords: Actinomycin D; barley; root growth; mitotic activity; total protein content; peroxidase activity; ACID; RNA; AUXIN